IN VITRO SHOOT ORGANOGENESIS AND PLANTLET REGENERATION IN BRINJAL (SOLANUM MELONGENA L) - S. V. BHAT; A.S. JADHAV; B. D. PAWAR; A. A. KALE; V.P. CHIMOTE; S. V. PAWAR (The Bioscan, 2013)
In vitro plant regeneration of brinjal genotype “Manjari Gota” was achieved using cotyledonary leave, nodal segment and shoot tip explants. Best regeneration was observed on MS medium supplemented with 2 mg/l 6benzylamino purine (BAP) and 1 mg/l kinetin, with regards to regeneration efficiency, days to callus initiation and number of shoots per explant. Among the explants used cotyledonary leaf pair showed highest shoot regeneration efficiency (100 %) followed by shoot tip (96. 66 %) and nodal segment (93.33 %). The highest numbers of shoots per explant (6.66) were obtained while using cotyledonary leaf pair explant. In vitro root initiation was obtained within 8 days of culture on MS medium supplemented with 0.5 mg/l indole butyric acid (IBA). In vitro rooted plantlets were successfully established in polycarbonated polyhouse with 100 % survival rate. This plant regeneration method can be very useful for genetic transformation of brinjal.